1995
DOI: 10.1007/bf00203390
|View full text |Cite
|
Sign up to set email alerts
|

Adenomyoepithelioma of the breast associated with low-grade adenosquamous and sarcomatoid carcinomas

Abstract: Six cases of invasive breast carcinoma with unusual morphological features are reported. The ages of the female patients ranged from 46 to 79 years (mean 60.5). All tumours had areas typical of an adenomyoepithelioma. In three cases adenomyoepithelioma gradually merged with low-grade adenosquamous carcinoma. In the other three patients a sarcomatoid carcinoma was associated with adenomyoepithelial areas. A common origin is proposed for these neoplasms, which extends the morphological spectrum of epi-myoepithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 26 publications
1
74
0
Order By: Relevance
“…Low-grade adenosquamous carcinoma has been reported to arise in association with a number preexisting lesions, including papillomata, adenomyoepitheliomata, RS/complex sclerosing lesions, and fibroepithelial tumors. 64,[66][67][68][69] This association has led some authors to suggest that such lesions represent precursors to LGASC 62 ; however, further studies are necessary to support such a theory.…”
Section: Low-grade Adenosquamous Carcinomamentioning
confidence: 99%
“…Low-grade adenosquamous carcinoma has been reported to arise in association with a number preexisting lesions, including papillomata, adenomyoepitheliomata, RS/complex sclerosing lesions, and fibroepithelial tumors. 64,[66][67][68][69] This association has led some authors to suggest that such lesions represent precursors to LGASC 62 ; however, further studies are necessary to support such a theory.…”
Section: Low-grade Adenosquamous Carcinomamentioning
confidence: 99%
“…In 1970, Hamperl [23] became the first to describe a primary breast adenomyoepithelioma. Since then, reported cases have frequently been presented in small numbers or as single case reports [1, 5, 7, 9-14, 16, 18, 22, 24, 26, 28, 29, 31, 33, 34, 36-44, 49, 50, 53, 55, 59, 62, 64-66, 68-70], and occasionally in larger series [20,32,45,48,60]. The age of the patients so far reported ranges from 24 to 82 years, with a mean of 58 years.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the adenomyoepitheliomas reported have been considered to be benign [10, 16, 19, 22-24, 26, 31, 32, 36, 48-50, 55, 58, 60, 62, 63, 66, 68], they can recur locally [7,20,28,32,37,42,45,48,53,60,64,69], progress subsequently to a (more) malignant state [20,28,32,42,45,53,60], and give rise to metastases [9,20,32,37,45,53,60,64]. Morphological features of malignancy that could predict the potential for local recurrence and/or metastasis are not well established.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that some of these tumors arise from a single cell with the potential for divergent differentiations. 2,9,10 It has also been proposed that the myoepithelial cell might have a role in this context, at least in some of these lesions. 2,11 In order to investigate this further, we have now analyzed a series of salivary gland-like tumors of the breast and their salivary/lacrimal gland counterparts, including pleomorphic adenomas, adenoid cystic carcinomas, and epithelial-myoepithelial tumors, using in situ triple immunofluorescence lineage/ differentiation tracing (isTILT) experiments, which allow direct observation of cells at different stages of differentiation.…”
mentioning
confidence: 99%
“…2,9,10 It has also been proposed that the myoepithelial cell might have a role in this context, at least in some of these lesions. 2,11 In order to investigate this further, we have now analyzed a series of salivary gland-like tumors of the breast and their salivary/lacrimal gland counterparts, including pleomorphic adenomas, adenoid cystic carcinomas, and epithelial-myoepithelial tumors, using in situ triple immunofluorescence lineage/ differentiation tracing (isTILT) experiments, which allow direct observation of cells at different stages of differentiation. By tracing the sequential expression of basal (K5 and K14), glandular (K7 and K18, K8/18), and epidermal-specific squamous keratin (K10) [12][13][14] in combination with p63 15,16 and discriminatory myoepithelial markers such as SMA, 7,[17][18][19] we can infer the developmental capacities of K5/K14-positive tumor cells and construct differentiation lineage trees for these tumor types.…”
mentioning
confidence: 99%